Development of Discovery Learning based Linktree Learning Media to Improve Geography Learning Outcomes in High School - Nera Afriyose; Sudjarwo; Sugeng Widodo (East Asian Journal of Multidisciplinary Research, 2022)
This research is motivated by the importance of using media in improving student learning outcomes. The purpose of this study was to test the effectiveness of the development of discovery learning-based linktree learning media to improve geography learning outcomes in high school. The type of research used in this research is Research and Development. This research uses ADDIE model development research including Analysis,Design, Development, Implementation, and Evaluation. The results of this study indicate: 1) The development of this learning media through the stages of ADDIE development, 2) The results of the feasibility test of experts with high categorization validity (very feasible) for material, media, language and learning design, 3) The results of the wide trial feasibility test show that there is an influence the use of discovery learning model linktree learning media has an effect on improving geography learning outcomes, and 4) the effectiveness test results show the use of discovery learning-based lintree learning media is effective for improving geography learning outcomes.